Mechanical skin injury promotes food anaphylaxis by driving intestinal mast cell expansion. - Leyva-Castillo, Juan-Manuel (Immunity, 2019)
Mast cell (MC) mediator release following crosslinking of surface-bound IgE antibody by ingested antigen underlies food allergy. However, IgE antibodies are not uniformly associated with food allergy, and intestinal MC load is an important determinant. Atopic dermatitis (AD), characterized by pruritis and cutaneous sensitization to allergens including foods is strongly associated with food allergy. Tape stripping mouse skin, a surrogate for scratching, caused expansion and activation of small intestinal mast cells (MCs), increased intestinal permeability, and promoted food anaphylaxis in sensitized mice. Tape stripping caused keratinocytes to systemically release interleukin-33 (IL-33) which synergized with intestinal tuft cell-derived IL-25 to drive the expansion and activation of intestinal type-2 innate lymphoid cells (ILC2s). These provided IL-4 that targeted MCs to expand in the intestine. Duodenal MCs were expanded in AD. In addition to promoting cutaneous sensitization to foods, scratching may promote food anaphylaxis in AD by expanding and activating intestinal MCs.